The Natural History of Pancreatic Cancer in Manitoba: A Population Based Study - Jack Martin; Brian H Weinerman (Canadian Journal of Gastroenterology)
Adenocarcinoma of the pancreas is a virulent malignancy. A retrospective study was undertaken to determine the natural history of the disease in Manitoba, and to examine which facets of the disease might predict survival. A retrospective review of the Manitoba Tumour Registry from January 1987 to December 1989 was performed. Two hundred and fourteen exocrine cases were identified, and known islet cell tumours, lymphomas and sarcomas were excluded. The variables analyzed were age, sex, surgical or radiological stage of disease, pathological differentiation, means of diagnosis and treatment. There were 112 females and 102 males with a median age of 73 years (80% of patients were older than 60 years). The mean survival from time of diagnosis was only six weeks. Univariate analysis identified male sex, advanced stages and poor differentiation as poor prognostic indicators. Multivariate analysis revealed that advanced stage and lack of differentiation were independent prognostic variables. Treatment, which was very selective, was also noted on univariate analysis to be a prognostic indicator but was not used in the multivariate regression analysis. The poor prognosis of all individuals confirms the rationale of trying to develop better treatments for all stages of disease, and stage and pathological differentiation should be taken into account when designing clinical trials.